STRATEGI PENINGKATAN KINERJA PELAYANAN PUBLIK DI KANTOR KECAMATAN MALALAYANG KOTA MANADO - Drakel, Zainul Fikri (HOLISTIK, Journal Of Social and Culture, 2019)
This study aims to determine the strategy of improving public service performance in the Malalayang District office in Manado City. From the results of the study show that the implementation of services in Malalayang District seen from the identification of internal environment and external environment include: strengths (weaknesses), (weakness), opportunities (opportunities), and threats (threaths), namely: (1) Strength (strength), the condition of service of the Malalayang District office is actually quite good, all are in accordance with the SOP and in accordance with the procedures required. Facilities and infrastructure are quite adequate to have a public room, and a front office, besides that it is also equipped with lactation room facilities, children's room, smoking area, and toilet. (2) Weakness (weakness), the human resources of the Malalayang Sub-district office have been placed in accordance with their competencies, except that it is necessary to add IT department HR who can use information technology so that they can provide effective and clear information and connect directly with the community. (3) Opportunities, participation is needed in improving services, because the government cannot work optimally without the support of the community and stakeholders. (4) Threaths, services that are considered to be lacking in terms of service counters that make visitors have to wait, because the space is full when the applicant's situation is crowded.Keywords: Strategy, Performance, Public Service.